The Concept of Merdeka Belajar from the View of Constructivism - Achmad Achmad Alfaruki (Islamic University of Indonesia, 2022)
The Minister of Education, Culture, Research, and Technology of the Forward Indonesia cabinet, Nadim Makarim, issued the Merdeka Belajar as a concept of national education in the disruption era. In Merdeka Belajar, Students are offeredÂ advantages and possibilities to study based on their interests and career aspirations. This study analyzed the concept of Merdeka Belajar from the view of constructivism. The constructivist paradigm aims to interpret the world, understand life, and create meaning. This library research aims to understand the philosophical paradigm of the concept of Merdeka Belajar. The results of this study were generated from relevant sources such as scientific journals, books, theses, and dissertations. This study reveals links between the concept of Merdeka Belajar and Constructivism that both emphasize freedom, flexibility, and independence for educational institutions. Students are not bound by strict rules. Knowledge can be obtained from everyday experience.